The working conditions of professional black women journalists: phase two - Zimu, Nokwazi (My University, 2012)
They make up 45% of the country’s population, but black women remain the most poorly represented group in the media. Often they are portrayed as victims of gender–based or domestic violence, villains or sex objects. At the same time black women remain the least successful professionals in the media industry. Studies show that they occupy only a mere six percent of senior managerial positions in the industry. Such representation of women workers in the country’s newsrooms has indeed had an effect on the portrayal of black women by the media. Using the SABC TV newsroom as a case study, I survey a group of ten women, three of whom, myself included, are no longer employed by the SABC. I further conduct interviews with five of the women, while five others participate in the Focus Group. Five women who represent the different black women news sources are also interviewed. The research is conducted by means of the qualitative and self-reflexive methods, supported by thematic content analysis. The study answers two questions relating to working conditions of the black women in the newsroom and the representation of black women as sources in the news bulletins. I take the argument from the first phase of my study forward, that the marginalisation of black women in the media lives on and there is an urgent need for women to stand together in the spirit of activism, to form a resistance movement aimed at fighting patriarchal practices in the industry.
M.A., Faculty of Humanities, University of the Witwatersrand, 2011